Method for preparing high-quality SnO2 amorphous-nanorod heterogeneous phase through ALD (atomic layer deposition) and application of high-quality SnO2 amorphous-nanorod heterogeneous phase

Growing SnO2 amorphous-nanocolumn heterophase through ALD technology solves the problem of cumbersome preparation methods and poor stability of existing SnO2 electron transport layer, achieving a higher quality electron transport layer, promoting carrier transmission and light absorption. Improves the performance of solar cells.

CN119403421AActive Publication Date: 2025-02-07YUNNAN UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411539986.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-07
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The existing SnO2 electron transport layer preparation method has cumbersome process, poor stability, difficult to control the morphology, and the use of chemical reagents is very contaminated and costly. The grown SnO2 film has many defects and is amorphous, which is not conducive to carrier transmission.

Method used

ALD technology is used to grow the heterogeneous phase of SnO2 amorphous-nanocolumns. By providing the substrate and pretreatment, spin-coating the tin oxide nanocrystal solution, plasma sputtering etching is performed, and tetraethyltin and H2O2 are used in ALD. As the reaction source, the reaction temperature and deposition rate are controlled to form a tin oxide amorphous-nanocolumn heterophase.

Benefits of technology

Simplified the SnO2 preparation process, reduced environmental pollution, and fewer internal defects of the prepared heterogeneous phase, promoted carrier transmission of perovskite batteries, reduced non-radiative recombination of the transport layer, and enhanced device light absorption, thereby improving The performance of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403421A_ABST
    Figure CN119403421A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a high-quality SnO2 amorphous-nanorod heterogeneous phase through ALD and application of the high-quality SnO2 amorphous-nanorod heterogeneous phase, and relates to the technical field of perovskite solar cells, the method comprises the following steps: S1, providing a substrate and pretreating the substrate to obtain a pretreated substrate; s2, spin-coating a tin oxide nanocrystalline solution on the pretreated substrate to obtain a pretreated film layer; s3, performing plasma sputtering etching on the surface of the pretreated film layer to obtain a first treated part; and S4, the first treated part is put into ALD to be preheated, tetraethyltin and H2O2 serve as reaction sources, tin oxide nanocrystals grow on the surface of the first treated part, the reaction temperature and the deposition speed of a cavity are controlled, the tin oxide amorphous-nanorod heterogeneous phase is obtained, and preparation is completed. The invention further comprises application of the method, and the method is used for preparing the perovskite solar cell. According to the method, the preparation process is simplified, the method is environment-friendly, the internal defects of the prepared heterogeneous phase are few, and the device performance is more excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of perovskite solar cells, and in particular to a method for preparing high-quality SnO2 amorphous-nanocolumn heterogeneous phase by ALD. Background Art

[0002] Perovskite solar cells widely use planar SnO2 polycrystals and nanocrystals, but perovskite cells based on planar electron transport layers cannot simultaneously achieve efficient solar light absorption and efficient photogenerated carrier transport. One-dimensional (1D) metal oxide (such as TiO2, ZnO and SnO2) nanocolumn structures can improve carrier transport between perovskite / transport layers as direct channels for electron transport. In addition, compared with mesoporous structures, one-dimensional nanocolumn structures are more conducive to the full filling of perovskites and can form a good heterojunction interface.

[0003] However, the SnO2 electron transport layer is usually prepared by solution method. This method is not only cumbersome in preparation process, poor in stability, and difficult to control the morphology, but also uses chemical reagents with high pollution and cost. Some studies have used tetraethyltin and H2O2 to deposit SnO2 thin films by ALD, but the grown SnO2 thin films have many defects and are amorphous, which is not conducive to carrier transport and has obvious defects. Summary of the invention

[0004] The purpose of the present invention is to solve the problems of complicated process, poor stability, difficult morphology control, large pollution and high cost of chemical reagents in the existing SnO2 electron transport layer preparation method. The present invention provides a method for growing SnO2 amorphous-crystalline nanocolumn heterogeneous phase by ALD. The SnO2 amorphous-crystalline heterogeneous phase prepared by the present invention can better promote carrier transport, reduce non-radiative recombination of the transport layer, enhance the light absorption of the device, and thus improve the performance of the device.

[0005] In order to achieve the above-mentioned purpose, the present invention specifically adopts the following technical solutions:

[0006] A method for preparing high-quality SnO2 amorphous-nanopillar heterogeneous phase by ALD, comprising the following steps: S1, providing a substrate and pre-treating it to obtain a pre-treated substrate; S2, spin-coating a tin oxide nanocrystal solution on the pre-treated substrate to obtain a pre-treated film layer; S3, plasma sputtering etching the surface of the pre-treated film layer to obtain a first treated part; S4, placing the first treated part in ALD for preheating, using tetraethyltin and H2O2 as reaction sources, growing tin oxide nanocrystals on the surface of the first treated part, controlling the chamber reaction temperature and deposition rate to obtain the tin oxide amorphous-nanopillar heterogeneous phase, and completing the preparation.

[0007] Furthermore, in S1, the substrate is a transparent conductive substrate that can withstand high temperatures above 150°C.

[0008] Furthermore, the S1 specifically includes providing a substrate and placing the substrate in a UV light and ozone cleaning machine for cleaning for 10 to 18 minutes.

[0009] Furthermore, in S2, the tin oxide nanocrystal solution is spin-coated on the substrate at a rotation speed of 2200-2400 rpm for 25-35 seconds, and annealed for 25-35 minutes after spin coating to a temperature of 145-155°C.

[0010] Furthermore, in S2, the tin oxide nanocrystal solution is a tin oxide nanocrystal aqueous solution with a concentration of 12 to 15 mg / ml.

[0011] Furthermore, in S3, the plasma sputtering etching uses nitrogen as an inert gas, with a flow rate of 900-1100 sccm, a chamber pressure of 1.3-1.45 torr, and a power of 700 w.

[0012] Furthermore, in S4, preheating is performed at 350° C. for 8 to 12 minutes.

[0013] Furthermore, in S4, the reaction temperature of the chamber is controlled to be 300-400° C., and the deposition rate is 0.05 nm / s.

[0014] Furthermore, the method further comprises performing heterogeneous phase surface modification on the tin oxide amorphous-nanopillar heterogeneous phase obtained in S4 to complete the preparation.

[0015] The present invention also provides an application of the method for preparing high-quality SnO2 amorphous-nanopillar heterophase based on the above-mentioned ALD, and the method is used for the preparation of perovskite solar cells.

[0016] Compared with the prior art, the advantages of the present invention are:

[0017] 1. The present invention relates to a method for preparing high-quality SnO2 amorphous-nanopillar heterophase by ALD. The present invention uses ALD to grow SnO2 amorphous-nanopillar heterophase as the electron transport layer of solar cells. The method simplifies the SnO2 preparation process and has little environmental pollution; the prepared heterophase has fewer internal defects and can promote carrier transport in perovskite cells. It can also reduce non-radiative recombination in the transport layer and enhance light absorption of the device, thereby improving the performance of the device.

[0018] 2. The application of the ALD method for preparing high-quality SnO2 amorphous-nanopillar heterophase involved in the present invention can be used in the preparation of perovskite solar cells. The preparation method is simple, has wide applicability, and has a large application space. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a schematic diagram of the nanocrystalline structure after the plasma sputtering etching of the tin oxide surface in Example 1 of the present invention.

[0020] Figure 2 Schematic diagram of the structure of the tin oxide amorphous-nanopillar heterogeneous phase in Example 1 of the present invention.

[0021] Figure 3 Scanning electron microscope image of the device 1 prepared in Example 1 of the present invention Figure 1 .

[0022] Figure 4 Scanning electron microscope image of the device 1 prepared in Example 1 of the present invention Figure 2 .

[0023] Figure 5 Schematic diagram comparing the energy conversion efficiency measurement results of device 1 and device 3 in Experimental Example 2 of the present invention.

[0024] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0025] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. DETAILED DESCRIPTION

[0026] The present invention provides a method for preparing high-quality SnO2 amorphous-nanopillar heterogeneous phase by ALD, comprising the following steps: S1, providing a substrate and pre-treating the substrate to obtain a pre-treated substrate; S2, spin-coating a tin oxide nanocrystal solution on the pre-treated substrate to obtain a pre-treated film layer; S3, plasma sputtering etching the surface of the pre-treated film layer to obtain a first treated part; S4, placing the first treated part in ALD for preheating, using tetraethyltin and H2O2 as reaction sources, growing tin oxide nanocrystals on the surface of the first treated part, controlling the reaction temperature and deposition rate of the chamber to obtain the tin oxide amorphous-nanopillar heterogeneous phase, and completing the preparation.

[0027] It can be understood that ALD uses tetraethyltin and H2O2 as sources to grow tin oxide nanocrystals, controls the chamber reaction temperature and deposition rate, and during the deposition process, crystal epitaxy occurs on the surface of tin oxide nanocrystals to form a nano-pillar structure; while the substrate without nanocrystals attached will grow disordered amorphous tin oxide. Finally, a tin oxide amorphous-nano-pillar heterogeneous phase is obtained.

[0028] In the prior art, the morphology of SnO2 grown by solution method is difficult to control, there are a lot of defects inside, and the ability to extract carriers is weak; the preparation process is complicated and pollutes the environment. The SnO2 film deposited by ALD directly using tetraethyltin and H2O2 has many defects and is amorphous, which is not conducive to carrier transport.

[0029] The preparation method of the present invention uses tin oxide nanocrystals as seed crystals and ALD grows SnO2 amorphous-nanopillar heterogeneous phase as the electron transport layer of the solar cell. This method simplifies the SnO2 preparation process and has less environmental pollution; the prepared heterogeneous phase has fewer internal defects and can promote carrier transport of perovskite cells and enhance the light absorption performance of the device.

[0030] In some embodiments of the present invention, in S1, the substrate is a transparent conductive substrate that can withstand high temperatures above 150°C.

[0031] In some specific embodiments, the substrate is preferably a FTO or ITO substrate.

[0032] In some embodiments of the present invention, the step S1 specifically includes providing a substrate and placing the substrate in a UV light and ozone cleaning machine for cleaning for 10 to 18 minutes. Specifically, the cleaning time is preferably 15 minutes.

[0033] In some embodiments of the present invention, in S2, the tin oxide nanocrystalline solution is spin-coated on the substrate at a rotation speed of 2200-2400 rpm, a spin-coating time of 25-35 s, and annealing is performed for 25-35 min after spin-coating, and the annealing temperature is 145-155° C. Specifically, the tin oxide nanocrystalline solution is spin-coated on the substrate at a rotation speed of preferably 2300 rpm, a spin-coating time of preferably 30 s, an annealing time of preferably 30 min after spin-coating, and the annealing temperature is 150° C.

[0034] In certain embodiments of the present invention, in S2, the tin oxide nanocrystal solution is a tin oxide nanocrystal aqueous solution with a concentration of 12 to 15 mg / ml. Specifically, the tin oxide nanocrystal solution is preferably a tin oxide nanocrystal aqueous solution with a concentration of 14 mg / ml. Tin oxide nanocrystals are commercially available from Shanghai Aladdin Biochemical Technology Co., Ltd., with an average particle size of <100 nm and a purity of 99.9%.

[0035] In some embodiments of the present invention, in S3, the plasma sputtering etching uses nitrogen as an inert gas, the flow rate is 900-1100 sccm, the chamber pressure is 1.3-1.45 torr, and the power is 700 W. Specifically, the plasma sputtering etching uses nitrogen as an inert gas, the flow rate is preferably 1000 sccm, the chamber pressure is preferably 1.4 torr, and the power is 700 W.

[0036] In certain embodiments of the present invention, in S4, preheating is performed at 350° C. for 8 to 12 minutes. Specifically, the preheating time is preferably 10 minutes.

[0037] In some embodiments of the present invention, in S4, the reaction temperature of the chamber is controlled to be 300-400° C., and the deposition rate is 0.05 nm / s.

[0038] In certain embodiments of the present invention, in S4, the reaction source H2O2 is 50 wt% H2O2.

[0039] In certain embodiments of the present invention, in S4, the reaction pressure using tetraethyltin and H2O2 as reaction sources is preferably 1.8 torr.

[0040] In certain embodiments of the present invention, the method further comprises performing heterogeneous phase surface modification on the tin oxide amorphous-nanopillar heterogeneous phase obtained in S4 to complete the preparation.

[0041] In certain embodiments of the present invention, the specific operation of heterogeneous phase surface modification is to use formamidine oxalate solution FOA to modify the heterogeneous phase surface. The concentration of the formamidine oxalate solution used is 3 mg / ml (the solvent is purified water). The specific operation of modification is to use the formamidine oxalate solution to spin on the surface of the tin oxide amorphous-nanopillar heterogeneous phase, the rotation speed is preferably 5000 rpm, and the spin coating time is preferably 30 s. After spin coating, annealing is performed on a 150°C hot stage for 10 min.

[0042] It can be understood that the use of formamidine oxalate solution (FOA) to modify the heterogeneous phase surface can passivate tin oxide, while also reducing the oxygen vacancies and tin interstitial defects on the SnO2 surface and the FA+ / Pb2+ defects of the perovskite, thereby achieving the effect of improving the overall performance of the device.

[0043] In some embodiments, the formamidine oxalate solution FOA can be replaced by other bottom interface passivation materials for normal perovskite cells.

[0044] The present invention also provides an application of the method for preparing high-quality SnO2 amorphous-nanopillar heterogeneous phase based on the ALD method described above, wherein the method is used for preparing perovskite solar cells. The method is simple, widely applicable, and has a large application space.

[0045] Example 1

[0046] 1.1 Device preparation process

[0047] In this embodiment, the specific operations are:

[0048] S1. Provide an FTO substrate and place it in a UV light and ozone cleaning machine for cleaning for 15 minutes.

[0049] S2, spin coating the tin oxide nanocrystal solution on the substrate, the rotation speed is preferably 2300rpm, the spin coating time is preferably 30s, the annealing time after spin coating is preferably 30min, and the annealing temperature is 150°C to obtain a pre-treated film layer. S3, plasma sputter etching is performed on the surface of the pre-treated film layer, nitrogen is used as an inert gas, the flow rate is preferably 1000sccm, the chamber pressure is preferably 1.4torr, and the power is 700w. The first treated part is obtained, and the first treated nanocrystal structure after etching is as follows Figure 1 shown.

[0050] S4, placing the first processing piece in ALD for preheating at 350° C. for 10 minutes. Using tetraethyltin and H2O2 as reaction sources, grow tin oxide nanocrystals on the surface of the first processing piece.

[0051] The reaction temperature of the chamber is controlled to be 300-400℃, and the deposition rate is 0.05nm / s. During the deposition process, the surface of the tin oxide nanocrystal undergoes crystal epitaxy to form a nanocolumn structure; while the substrate without the nanocrystals attached will grow disordered amorphous tin oxide. Figure 2 The tin oxide amorphous-nanopillar heterophase is shown.

[0052] S5. After step S4, there are defects on the surface of the tin oxide amorphous-nanopillar heterogeneous phase prepared by ALD. Use formamidine oxalate to modify the heterogeneous phase surface. Use formamidine oxalate solution to spin on the surface of the tin oxide amorphous-nanopillar heterogeneous phase, the rotation speed is preferably 5000rpm, and the spin coating time is preferably 30s. After spin coating, anneal on a 150℃ hot stage for 10min. Complete the preparation of device 1.

[0053] Comparative Example 1

[0054] The device 2 is obtained by using SnO2 grown by the solution method commonly used in the prior art. The preparation method is as follows:

[0055] (1) Mix 275 mg SnC, 12.2 mL H2O, 1.25 mL HCl, 1.25 g urea, and 25 μL TGA in 100 mL deionized water.

[0056] (2) Immerse the FTO glass (only FTO glass) that has been cleaned in a UV light and ozone cleaning machine for 15 minutes in the above solution. Heat the solution in a 90°C oven for ≈4h (tin oxide polycrystals grow on the FTO surface during this process).

[0057] (3) The tin oxide polycrystalline FTO glass was taken out from the solution, ultrasonicated in deionized water and isopropanol for 5 minutes respectively, and then dried with an air gun.

[0058] (4) The glass was annealed in air at 170°C (humidity = 25-35%) for 60 minutes to obtain device 2. Experimental Example 1 The device 1 prepared in Example 1 was characterized by scanning electron microscopy.

[0059] 1.1 Test operation

[0060] The device 1 prepared in Example 1 was characterized by scanning electron microscopy. Figure 3 , Figure 4 .

[0061] 1.2 Results Analysis

[0062] See also Figure 3 and Figure 4 From the electron microscope image, it can be clearly seen that the surface structure of the device 1 prepared in Example 1 of the present invention is uniform, and a clear and uniform tin oxide amorphous-nanopillar heterogeneous phase structure can be seen on the surface. From the electron microscope image, the device 1 prepared in Example 1 of the present invention has an excellent structural morphology.

[0063] Experimental Example 2 Performance Test of Device 1 and Device 2 Prepared in Example 1 and Comparative Example 2.1 Experimental Operation

[0064] The energy conversion efficiency (PCE) of the device 1 prepared in Example 1 and the device 2 prepared in the comparative example were measured respectively. The measurement results are shown in Figure 5 .

[0065] 2.2 Results Analysis

[0066] See also Figure 5 As can be seen from the measurement result diagram, the device 1 prepared in Example 1 has a higher energy conversion efficiency and better performance than the device 2 prepared in the conventional method in the comparative example. It can be seen that the preparation method of this case is more superior.

[0067] In summary, the present invention relates to a method for preparing high-quality SnO2 amorphous-nanopillar heterophase by ALD, which uses tin oxide nanocrystals as seed crystals and grows SnO2 amorphous-nanopillar heterophase by ALD as the electron transport layer of solar cells. This method simplifies the SnO2 preparation process and has little environmental pollution; the prepared heterophase has fewer internal defects and can promote carrier transport of perovskite cells and enhance the light absorption performance of the device. As shown in Experimental Examples 1 and 2, the prepared device heterophase has fewer internal defects and better device performance.

[0068] The above embodiment is only one implementation of the present invention, and its description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. A method for preparing high-quality SnO2 amorphous-nanopillar heterogeneous phase by ALD, characterized in that: The following steps are involved: S1. providing a substrate and pre-treating the substrate to obtain a pre-treated substrate; S2, spin coating a tin oxide nanocrystal solution on the pretreated substrate to obtain a pretreated film layer; S3, performing plasma sputtering etching on the surface of the pre-treated film layer to obtain a first treated part; S4. Place the first processing piece in ALD for preheating, use tetraethyltin and H2O2 as reaction sources, grow tin oxide nanocrystals on the surface of the first processing piece, control the chamber reaction temperature and deposition rate to obtain a tin oxide amorphous-nanopillar heterogeneous phase, and complete the preparation.

2. The method for preparing high-quality SnO2 amorphous-nanopillar heterogeneous phase by ALD according to claim 1, characterized in that: In the above S1, the substrate is a transparent conductive substrate that can withstand high temperatures above 150°C.

3. The method for preparing high-quality SnO2 amorphous-nanopillar heterogeneous phase by ALD according to claim 1, characterized in that: Specifically, S1 is to provide a substrate and place the substrate in a UV light and ozone cleaning machine for cleaning for 10 to 18 minutes.

4. The method for preparing high-quality SnO2 amorphous-nanopillar heterogeneous phase by ALD according to claim 1, characterized in that: In S2, the tin oxide nanocrystal solution is spin-coated on the substrate at a rotation speed of 2200-2400 rpm for 25-35 seconds. After the spin-coating, annealing is performed for 25-35 minutes until the annealing temperature reaches 145-155°C.

5. The method for preparing high-quality SnO2 amorphous-nanopillar heterogeneous phase by ALD according to claim 4, characterized in that: In S2, the tin oxide nanocrystal solution is a tin oxide nanocrystal aqueous solution with a concentration of 12 to 15 mg / ml.

6. The method for preparing high-quality SnO2 amorphous-nanopillar heterogeneous phase by ALD according to claim 1, characterized in that: In S3, the plasma sputtering etching uses nitrogen as an inert gas, the flow rate is 900-1100 sccm, the chamber pressure is 1.3-1.45 torr, and the power is 700w.

7. The method for preparing high-quality SnO2 amorphous-nanopillar heterogeneous phase by ALD according to claim 1, characterized in that: In the above S4, preheating is performed at 350°C for 8 to 12 minutes.

8. The method for preparing high-quality SnO2 amorphous-nanopillar heterogeneous phase by ALD according to claim 1, characterized in that: In the above S4, the reaction temperature of the chamber is controlled to be 300-400° C., and the deposition rate is 0.05 nm / s.

9. The method for preparing high-quality SnO2 amorphous-nanopillar heterogeneous phase by ALD according to claim 1, characterized in that: The method further comprises performing surface modification on the tin oxide amorphous-nano-column heterogeneous phase obtained in S4 to complete the preparation.

10. Application of the method for preparing high-quality SnO2 amorphous-nanopillar heterogeneous phase by ALD according to any one of claims 1 to 9, characterized in that: The method is used for preparing perovskite solar cells.

Citation Information

Patent Citations

  • Preparation method of tin oxide layer, perovskite battery, preparation method of perovskite battery and power utilization device

    CN118042904A

  • 3D scanner using raspberry module

    KR102612909B1

  • Thin film interface control method through electron transport layer using plasma ALD

    KR102657093B1

  • Alternating etch and passivation process

    US20220208551A1